The feminism of Engels in The Origin of the Family, Private Property and the State - Aguirre Horno, Helena (Filosofia, ara! Revista per a pensar, 2018)
Engels denounces the situation of women in the bourgeois family and thinks that with the arrival of socialism their situation will radically improve.